The role of MSX1 in tooth agenesis in Iranians - MASSOUD SEIFI, BAHRAM KAZEMI, & PARISA GOLKAR (IAPD and Blackwell, 2007)
Advances in molecular biology, epidemiology, quantitative analysis, and developmental biology have made it possible to identify genes involved in traits important in dental disorders.